2023
DOI: 10.1002/dad2.12466
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of dementia in people with hypertension in the UK 2000 to 2021

Abstract: INTRODUCTIONWe investigated trends in the incidence of dementia in UK adults with hypertension.METHODSPrimary care electronic health records from IQVIA Medical Research Data UK, previously known as THIN, were used to identify 2,133,118 adults aged ≥40 years with hypertension over 2000 to 2021. The annual incidence rate and average annual percentage change in recorded dementia diagnoses were estimated and stratified by sex, 10‐year age bands, Townsend deprivation quintiles and dementia subtype.RESULTSThe crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This selective prescription can introduce bias in studies that fail to adequately exclude the early years of follow-up. This phenomenon was observed in Adesuyan et al's study, where results lost significance following the exclusion of the first three years of follow-up (6).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This selective prescription can introduce bias in studies that fail to adequately exclude the early years of follow-up. This phenomenon was observed in Adesuyan et al's study, where results lost significance following the exclusion of the first three years of follow-up (6).…”
Section: Discussionmentioning
confidence: 74%
“…Several in vitro and pre-clinical studies have suggested that PDE5 inhibitors may offer protective effects against AD, Vascular dementia (VaD), and Lewy body dementia (LBD) (3). Additionally, three recent cohort studies have found that Sildenafil usage was associated with reduced risk of AD (4)(5)(6). However, despite efforts to minimise bias, these studies remain susceptible to inherent methodological limitations of observational research, such as reverse causality and residual confounding, which could account for the observed protective effects (7).…”
Section: Introductionmentioning
confidence: 99%